2020
DOI: 10.1111/jfpp.14643
|View full text |Cite
|
Sign up to set email alerts
|

Sensory profiling and mapping of gluten‐free cookies made from blends Cardaba banana flour and starch

Abstract: Sensory profiling of gluten‐free (GF) cookies made from cardaba banana flour and starch blends were evaluated using trained panelists/assessors. The sensory attributes used to separate the cookie samples were appearance, aroma, taste, and texture/crispiness of the cookies. Sensory mapping (internal and external preference mapping) was evaluated using multidimensional scaling of data obtained using a 9‐point hedonic scale. Analysis of the panelists revealed the rating of the cookie samples was not affected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Their physical inaccessibility form is responsible for their resistant nature as found in partly milled seeds and grains in addition to some densely starchy foods that have been processed. Chemically, their measurement is determined as a disparity between released glucose produced by the digestive enzyme of a food sample that has been homogenized and boiled and the one released from a sample that is not boiled and homogenized ( Olawoye and Gbadamosi, 2020a , Olawoye and Gbadamosi, 2020b ). The heat stability of RS 1 in the majority of normal cooking processes is responsible for its use extensively as ingredients in conventional foods ( Sajilata et al., 2006 ).…”
Section: Dietary Fibrementioning
confidence: 99%
See 1 more Smart Citation
“…Their physical inaccessibility form is responsible for their resistant nature as found in partly milled seeds and grains in addition to some densely starchy foods that have been processed. Chemically, their measurement is determined as a disparity between released glucose produced by the digestive enzyme of a food sample that has been homogenized and boiled and the one released from a sample that is not boiled and homogenized ( Olawoye and Gbadamosi, 2020a , Olawoye and Gbadamosi, 2020b ). The heat stability of RS 1 in the majority of normal cooking processes is responsible for its use extensively as ingredients in conventional foods ( Sajilata et al., 2006 ).…”
Section: Dietary Fibrementioning
confidence: 99%
“…A major reason for this supplement is that dietary fibre produces a wide variety of flavours for the products making it attractive and more palatable. Great importance is their fermenting abilities as they can ferment and give a better structure and a more attractive end product ( Olawoye and Gbadamosi, 2020a , Olawoye and Gbadamosi, 2020b ). The most important factor is that they are cost-efficient.…”
Section: Food Applicationsmentioning
confidence: 99%
“…Gluten-free products' marketability is estimated to increase in value from US$ 4.18 billion in 2017 to US$ 6.47 billion by 2023 in which gluten-free bread and cookie are estimated to be the most consumed cereal-based GF-food globally [9]. During the production of food products made from gluten, gluten present in the food products is responsible for the elasticity, extensivity and texture resistant if the dough [2,12]. However, to improve the quality (texture and specific volume) of gluten-free diet/products, hydrocolloids such as hydroxypropylmethylcellulose, xanthan gum, pectin, carboxymethylcellulose are commonly used to improve the baking quality, imparting texture and appearance as well as stability in the gluten-free dough.…”
Section: Introductionmentioning
confidence: 99%
“…This SCFA provides the body with additional energy as well as a high concentration of butyrate which is also beneficial in the reduction of colon cancer. Hence, it had been suggested that for health benefits, starch-baked food high in slowly digestible starch and resistant starch should be consumed ( Olawoye and Gbadamosi, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies to improve the overall nutritional and sensorial characteristics of gluten-free products had been carried out ( Malgor et al., 2020 ; Olawoye and Gbadamosi, 2020c ; Rybicka et al., 2019 ). Owing to this, cookie could serve as a potentially nutritious gluten-free snack through careful selection of ingredients.…”
Section: Introductionmentioning
confidence: 99%